NATIONAL SONGS AS PEDAGOGICAL DISCOURSE: AN INTERPERSONAL AND APPRAISAL ANALYSIS - Siska Eka Syafitri; Maria Ulfa (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
Although national songs serve as powerful cultural and social tools, limited research in Indonesia has examined how their linguistic features construct interpersonal meaning within Systemic Functional Linguistics (SFL) and pedagogical discourse. This study investigates the interpersonal metafunction in Indonesian national songs and explores its pedagogical implications. Employing a qualitative discourse-analytic design, the study analyzes clauses as the unit of analysis from seven widely recognized Indonesian national songs. Drawing on Halliday’s interpersonal metafunction and Martin & White’s appraisal theory, the analysis systematically codes pronoun systems, mood types, modality markers, and attitudinal lexis. Analytical reliability was supported through iterative coding and cross-text comparison to ensure consistency of interpretation. The findings indicate that inclusive pronouns (kita, kami), persuasive declarative and imperative moods, and high-value evaluative lexis (e.g., merdeka, jaya) work together to construct solidarity, authority, and emotional alignment. These patterned linguistic resources position national songs as implicit pedagogical discourse that models civic identity and collective responsibility. The study demonstrates how culturally embedded texts can be strategically integrated into language pedagogy to support socio-emotional learning, cultural literacy, and civic value formation.